From Anti-Racism to Critical Race Theory in Ontario Public Schools - Tyndall, Regan; Raza, Kashif (Journal of Critical Race Inquiry)

(untitled) (Queen's University, 2024)
The distortion of Critical Race Theory (CRT) in American popular media has spread to Canada, where the word “race” has traditionally been avoided in education, but where incidents involving race and “anti-racism” now garner considerable attention. We outline CRT in education and the context surrounding anti-racism work in Ontario. We then analyze important initiatives, such as Ontario’s proposed Bill 16 and the Hamilton-Wentworth District School Board’s “Learn. Disrupt. Rebuild.” module, in terms of their relevance within the CRT theoretical framework. Basic qualitative content analysis shows that the much-discussed provincial-level Bill 16 does not reflect the tenets of CRT—despite what its opponents, notably organizations such as Parents As First Educators (PAFE), have argued. However, the district-level “Learn. Disrupt. Rebuild.” initiative does reflect some tenets of CRT. This latter equity initiative is suggested as a model, starting from the local level in school districts, that other Canadian educators supportive of CRT should feel justified in following, as progressive Canadian districts move from anti-racism towards the next phase of district reform.